2019
DOI: 10.1038/s41598-019-48247-5
|View full text |Cite
|
Sign up to set email alerts
|

High rates of maternal depression amongst Syrian refugees in Lebanon - a pilot study

Abstract: This pilot study compares symptoms of depression and risk factors amongst Syrian refugees and low-income Lebanese mothers accessing a primary care centre in Beirut between January and June 2018. Women who gave birth in the previous two years or who were currently pregnant were included in the study. Depressive symptoms were assessed using the Arabic Edinburgh Postnatal Depression Scale (EPDS). Correlations between EPDS score and sociodemographic and mental health variables were analysed using Pearson’s coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…However, previous studies reported social support in mother migrated from Syria affected duration of breastfeeding and age-appropriate feeding attitudes in Turkey [ 31 , 50 ]. In addition, similar to our study, maternal depression were reported to be high in Syrian refugee mothers in Lebanon [ 51 ] and Turkey [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, previous studies reported social support in mother migrated from Syria affected duration of breastfeeding and age-appropriate feeding attitudes in Turkey [ 31 , 50 ]. In addition, similar to our study, maternal depression were reported to be high in Syrian refugee mothers in Lebanon [ 51 ] and Turkey [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our findings correspond with previous studies showing a high prevalence of perinatal depression among Syrian refugees in Lebanon and Jordan (74% and 50% respectively) as well as in Canada (58%) (Stevenson et al, 2019;Mohammad et al, 2018;Bowen et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Comparable and higher prevalence were reported among Palestinian and Syrian refugees in Lebanon (72,(87)(88)(89)(90) . A strong relationship was observed between poor maternal mental health, food insecurity, and a high crowding index in our findings.…”
Section: Discussionmentioning
confidence: 85%